Valor genético predito em função do coeficiente de endogamia e geração em duas populações de codornas - Alves, Álisson Verbenes (2019)
The objective was to evaluate the genetic value of two populations of quails according to the coefficient of inbreeding and generations. Two pedigrees of quails of the species Coturnix coturnix coturnix were analyzed: EV1 and EV2 bred under conditions of random mating and under selection pressure for characteristic body weight. The inbreeding coefficients and the genetic value of the animals were calculated according to the methodology described in the WOMBAT program (Meyer, 2007); for birth weight weighing, seven, 14, 21, 28 and 35 days of age. Estimates of inbreeding depression were obtained through records with a non-zero inbreeding coefficient and the respective genetic value were submitted to regression analysis by the SAS Studio software, through PROC REG including the effect of generations on the analyzes. When a quadratic or linear effect was found for the inbreeding coefficient and a linear effect for generations, the genetic values were organized in a response surface graph. A curvilinear effect was observed for the inbreeding coefficient in both populations.